2008
DOI: 10.1007/s00520-007-0380-2
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and treatment burden associated with cancer treatment: results from a cross-sectional national survey in the U.S.

Abstract: In addition to the symptomatic experience of side effects, patients reported a considerable time burden for treatment. It is important to consider supportive care strategies that may effectively reduce side effects and their associated treatment burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
235
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 322 publications
(263 citation statements)
references
References 43 publications
13
235
0
9
Order By: Relevance
“…We found fatigue, nausea, intestinal disorders and hand-foot syndrome to be the most common symptoms reported by next of kin. This is confirmed by other studies investigating patients (Aprile et al, 2008;Berger et al, 2010;Goldberg et al, 2007;Griffin-Sobel, 2006;Hallquist Viale and Sommers, 2007;Henry et al, 2008;Kearney et al, 2008). However, the next of kin reported that nausea worsened with every treatment, whereas other studies on patients, in contradiction, have found that nausea decreases after every treatment (Henry et al, 2008;Kearney et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We found fatigue, nausea, intestinal disorders and hand-foot syndrome to be the most common symptoms reported by next of kin. This is confirmed by other studies investigating patients (Aprile et al, 2008;Berger et al, 2010;Goldberg et al, 2007;Griffin-Sobel, 2006;Hallquist Viale and Sommers, 2007;Henry et al, 2008;Kearney et al, 2008). However, the next of kin reported that nausea worsened with every treatment, whereas other studies on patients, in contradiction, have found that nausea decreases after every treatment (Henry et al, 2008;Kearney et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…The side effects of chemotherapy vary depending on the agents used: myelosuppression, nausea, diarrhoea, neurotoxicity and hand-foot syndrome have been reported (Berger et al, 2010;Hallquist Viale and Sommers, 2007). The worst and most distressing side effect reported of chemotherapy for patients with CRC is fatigue (Berger et al, 2010;Henry et al, 2008;Kearney et al, 2008, Stone et al, 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in this sphere have described the components of treatment burden in a limited way, for example, in relation to individual treatment adverse effects, 20,21 or have included very small numbers of participants. 2 The research has therefore not provided a picture of the entire treatment burden experienced by patients, often excluding those with comorbidities, 22 who represent almost one-half of all patients with chronic disease.…”
Section: T R E At Men T Bur Den O F Chronic He a R T Fa Ilur Ementioning
confidence: 99%
“…It has been described as an unexpected tiredness that is more intense and severe than the fatigue experienced in healthy people 3 . Cancer-related fatigue can affect up to 80%-90% of cancer patients, and it can occur before diagnosis, during cancer treatment, and after completion of cancer therapies 1,[4][5][6][7][8][9] . The origin of cancer-related fatigue is multifactorial: it can be a result of the cancer itself, of cancer treatments, and of comorbid medical and psychological conditions 10,11 .…”
Section: Introductionmentioning
confidence: 99%